Common omissions and misconceptions of wave propagation in turbulence: discussion - Charnotskii, Mikhail (Journal of the Optical Society of America. A, Optics, image science, and vision, 2012)
This review paper addresses typical mistakes and omissions that involve theoretical research and modeling of optical propagation through atmospheric turbulence. We discuss the disregard of some general properties of narrow-angle propagation in refractive random media, the careless use of simplified models of turbulence, and omissions in the calculations of the second moment of the propagating wave. We also review some misconceptions regarding short-exposure imaging, propagation of polarized waves, and calculations of the scintillation index of the beam waves.